Hurufi Poet Vahdeti Bosnevi and His Divan (Prilozi za orijentalnu filologiju, 2017)
Although the heretic Hurufi sect, founded at the end of the 14th century in Iran, was from the very beginning exposed to ruthless persecutions, it survived until the middle of the 17th century, while its religious learning, modified and adapted to the learning of other brotherhoods (especially the Bektashi one) was maintained until the present day. By interpreting Kur'an in a highly esoteric way, (where very important issues were numeral values  of particular letters of the Arabic-Persian alphabet and their mutual relations (thus the name „Hurufi“ ḥurûf-ar  letters) as well as the search for equivalents to these letters in the human face as the „second book of God“, the members of the sect provoked anger of religious puritans and representatives of official orthodoxy, this causing their tragic destiny, so that the founder of the order himself, Fazlullah Esterbadi was murdered in 1394.In the notorious persecutions of heretic and mystic brotherhoods in Bosnia in the middle of the 16th c., both Bosnian Hamzevis and Hurufis were destroyed. A member and apologist of this sect was Ahmed Vahdeti, „the quarrelling poet“ and wanderer (though not always of his own free will), who sent satires and mock-poems from his native Dobrun to representatives of the authorities and the ortodox ulema, by whom he was probably given his pejorative name „mülḥid“ - „the schismatic“.